PERAN KOPERASI DALAM RANGKA PEMBERDAYAAN EKONOMI MASYARAKAT TERPAPAR PADA KAWASAN RAWAN BENCANA DI WILAYAH KABUPATEN TUBAN - Nihayatus Sholichah dan Mesak Paidjala (Lembaga penelitian dan Pengembangan Masyarakat (LPPM) IAIN Kediri, 2017)
As the one of populist economy institute in Indonesia, cooperatives have been grown and developed almost inthe most of territory in Indonesia. No exception, probability there are also many cooperatives within the disasterprone territories or region. So that the existence of cooperatives in disaster prone area will be the pedestaland hope of local society to come into play and help quickly to give stimulant recovery and society economyempowerment, in the moment when the societies get disaster.Cooperative is one of institute that can participate together with society in the disaster risk management. As theinstitute that is established together and based on kinship, cooperatives are hoped be the nearest institute withcitizen so that can result best solutions to overcome disaster problem.There are various manners that can be done cooperatives to help the society to decrease the disaster impact; oneof them is to prepare reserve stock for emergency needs. Because of still in the region that is prone of disaster,the stocks should be stored in the save place. These reserve stocks can be taken from SHU (effort remainingresults) appropriated to the agreement, so that it can be given freely while wait the help from outsiders. So onthe other word cooperatives have the function as the provider of emergency needs after disaster so the needs ofvictims (the societies around cooperative) can be fulfilled quickly.Keywords: Cooperative, Economy Empowerment, Disaster Prone Region